2015
DOI: 10.1080/00220388.2014.976616
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Conflict Exposure during Formative Years on Labour Market Outcomes in Tajikistan

Abstract: This study explores the effect of the 1992-1998 armed conflict in Tajikistan on the labour market outcomes by gender. The focus is on cohorts that were of school age during the conflict or recently entered the labour force. The regression analysis controls for the cohort and district-level exposure to conflict. Younger women but not men who also lived in regions more affected by conflict were at least 10 percentage points more likely to be employed than similarly aged women from lesser affected districts. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Third, it may be due to a change in women's work preference to support themselves and their families. For example, Shemyakina (2015) indicated a shift in the labor market outcome by gender after exposure to the 1992-98 armed conflict in Tajikistan. Further, Fernández, Ibáñez, and Peña (2014) suggested that females who experienced violent shocks in rural Colombia decreased their leisure time and increased the time devoted to household chores and caring for children and other family members.…”
Section: First-stage Regression (Intifada and Parents' Education)mentioning
confidence: 99%
“…Third, it may be due to a change in women's work preference to support themselves and their families. For example, Shemyakina (2015) indicated a shift in the labor market outcome by gender after exposure to the 1992-98 armed conflict in Tajikistan. Further, Fernández, Ibáñez, and Peña (2014) suggested that females who experienced violent shocks in rural Colombia decreased their leisure time and increased the time devoted to household chores and caring for children and other family members.…”
Section: First-stage Regression (Intifada and Parents' Education)mentioning
confidence: 99%
“…Survey data shows that Ugandan adults who were abducted as children by rebel groups and forced to become soldiers in the rebel army during Uganda's 1990s civil war had attained almost one year less of schooling, were half as likely to be working in a skilled job, and had onethird less annual earnings (Blattman and Annan, 2010). In Tajikistan's 1992-1998 civil war, on the other hand, younger women (defined as those who were of school age or who had recently entered the labor force) exposed to the conflict were 10 percent more likely to be employed than were women the same age who lived in regions that had experienced less conflict (Shemyakina, 2015a). There were no such effects for men, nor were there effects on wages for men or women.…”
Section: Labor Marketmentioning
confidence: 99%
“…A growing body of literature shows that adverse events such as civil conflicts during infancy and in utero may result in deleterious consequences not only in the immediate term but also in adulthood. In addition to studies that have shown the immediate effects of conflict on health, nutrition, birth weight and education (Ichino and Winter-Ebmer, 2004;Akresh et al, 2012a;Akresh et al, 2012b;Oskorouchi, 2019;Akbulut-Yuksel, 2014;Shemyakina, 2011, Brown, 2018, there is evidence which links early-life exposure to conflict with reduced earnings, lower labour market participation and worse fertility outcomes in later-life (Islam et al, 2016;Shemyakina, 2015;Kraehnert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%